MASYARAKAT DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Viki Insana; Lydia Sartika (Jurnal Al Athfaal, 2023)
Islamic Educational Philosophy is the mother of knowledge. Society is always described as a collection of human individuals who have similarities, both in characteristics and goals. In Islam, community members have equality in rights and obligations, Islam does not recognize caste and the granting of special rights to a person or group of someone's glory in Islamic society is only because of his devotion to Allah. In general, the characteristics of Islamic society have three characteristics, namely returning to Allah, prioritizing piety, and mutual respect for fellow community members. The basics of forming an Islamic society are Brotherhood, Compassion, Equality, Freedom, and Social Justice. The relationship between the philosophy of Islamic education and society is very closely related and the relationship is very large, like a symbiosis that cannot be separated from one another. Therefore, the Islamic community plays a very important role and is responsible for making a complete Muslim and civilized Islamic society as well as an ideal Muslim or society according to the guidance of the Qur'an and As-Sunnah.